Valence-shell photoelectron circular dichroism of ruthenium(iii)-tris-(acetylacetonato) gas-phase enantiomers. Issue 42 (20th October 2021) - Darquié, Benoît; Saleh, Nidal; Tokunaga, Sean K.; Srebro-Hooper, Monika; Ponzi, Aurora; Autschbach, Jochen; Decleva, Piero; Garcia, Gustavo A.; Crassous, Jeanne; Nahon, Laurent
Abstract : Mirror-image VUV photoelectron circular dichroism spectra (PECD) of the propeller-type chiral Ru(acac)3 enantiomers were measured with asymmetries up to 14%, suggesting that PECD is a universal mechanism, inherent to any type of chirality. Abstract : Chiral transition-metal complexes are of interest in many fields ranging from asymmetric catalysis and molecular materials science to optoelectronic applications or fundamental physics including parity violation effects. We present here a combined theoretical and experimental investigation of gas-phase valence-shell photoelectron circular dichroism (PECD) on the challenging open-shell ruthenium(iii )-tris-(acetylacetonato) complex, Ru(acac)3 . Enantiomerically pure Δ- or Λ-Ru(acac)3, characterized by electronic circular dichroism (ECD), were vaporized and adiabatically expanded to produce a supersonic beam and photoionized by circularly-polarized VUV light from the DESIRS beamline at Synchrotron SOLEIL. Photoelectron spectroscopy (PES) and PECD experiments were conducted using a double imaging electron/ion coincidence spectrometer, and compared to density functional theory (DFT) and time-dependent DFT (TDDFT) calculations. The open-shell character of Ru(acac)3, which is not taken into account in our DFT approach, is expected to give rise to a wide multiplet structure, which is not resolved in our PES signals but whose presence might be inferred from the additional striking features observed in the PECD curves. Nevertheless, the DFT-based assignment of the electronic bands leads to the characterisation of the ionized orbitals. In line with other recent works, the results confirm that PECD persists independently on the localization and/or on the achiral or chiral nature of the initial orbital, but is rather a probe of the molecular potential as a whole. Overall, the measured PECD signals on Ru(acac)3, a system exhibiting D 3 propeller-type chirality, are of similar magnitude compared to those on asymmetric-carbon-based chiral organic molecules which constitute the vast majority of species investigated so far, thus suggesting that PECD is a universal mechanism, inherent to any type of chirality.